2011
DOI: 10.1007/s00066-010-2166-6
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Supplementation in Cancer Therapy

Abstract: The observations suggest that EPA is not only a nutritional adjuvant but also may be a potential candidate to enhance the efficacy of irradiation on human cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…( Das et al, 1998 ; Colquhoun, 2009 ; Moon, 2023 ). Since ionizing radiation also generates ROS, which leads to lipid peroxidation of PUFAs, lipid peroxidation may be further enhanced in the membranes of EPA-rich tumor cells, and thus the combination of EPA and radiotherapy may cause additional damage to tumor cells ( Manda et al, 2011 ; Zaloga, 2021 ). This seems to provide a strong explanation for the fact that EPA can enhance the sensitivity of radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…( Das et al, 1998 ; Colquhoun, 2009 ; Moon, 2023 ). Since ionizing radiation also generates ROS, which leads to lipid peroxidation of PUFAs, lipid peroxidation may be further enhanced in the membranes of EPA-rich tumor cells, and thus the combination of EPA and radiotherapy may cause additional damage to tumor cells ( Manda et al, 2011 ; Zaloga, 2021 ). This seems to provide a strong explanation for the fact that EPA can enhance the sensitivity of radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…FABP7 plays different roles in the cell depending on which ligand it is bound to [34,66,67]. DHA has previously been shown to inhibit the migration of FABP7-expressing GBM cells [34,35], as well as sensitize GBM cells to chemotherapy and radiation in vitro [32,37,68,69]. It is already known that dietary DHA can affect the fatty acid composition of lipids in brain tissue [70][71][72], opening the door to the possibility that GBM patient outcome could be improved by increasing the DHA content in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in rats bearing Ward colon tumor under a cyclical regimen of CPT-11/5-fluorouracil (5-FU) where supplementation with fish oil inhibited tumor growth by raising its chemo-sensitivity and thus decreasing body weight loss, anorexia, and muscle wasting (Xue et al, 2009). Another study has proved the influence of EPA supplementation on the radio-sensitivity of colon adenocarcinoma cells HT-29 by increasing the extent of the LPO caused by radiation (Manda et al, 2011). CRC patients under chemotherapy enrolled in a prospective randomized fish oil supplementation and placebo-controlled study showed reduced CRP/albumin ratio, without changes in inflammatory cytokine profile, suggesting a reduction in the rate of development inflammatory and nutritional complications, and limiting the weight loss, suggesting that supplementation with these compounds is advisable during CRC treatment (Mocellin et al, 2013) ( Figure 1 ).…”
Section: Omega-3 Pufa Supplementation and Development Of Colorectal Cmentioning
confidence: 99%